Pengaruh socio-economy patriarki, pendidikan akhir dan pengangguran terhadap TPAK perempuan di Indonesia perspektif ekonomi Islam - Reza, Aditya Okta; Anggraeni, Erike; Nurmalia, Gustika (AL-Muqayyad, 2024)
In the framework of Islamic economics, every individual is guaranteed equal opportunities to access education and employment, provided that it does not violate Islamic legal principles. The concept of justice in Islamic economics serves to establish a prosperous and equitable society. This study aims to analyze the influence of socio-economic patriarchal cultural values, the level of educational attainment, and the unemployment rate on women's labor force participation rate (TPAK) in Indonesia from an Islamic economics perspective. The research employs panel data from 34 provinces in Indonesia using a saturated sampling method. Data analysis was conducted using EViews 10 software. The findings reveal that socio-economic patriarchal cultural values, educational attainment, and unemployment rates collectively influence women's labor force participation rates in Indonesia. From an Islamic economics perspective, increasing women's participation in the workforce can be achieved by encouraging their involvement in economic activities, motivating them to work, and improving their access to education and career opportunities.